Ideology, Maqāṣid, and Politics: The Paradox of Al-Qaraḍāwī’s Islamist Thought - Sulaiman, Akhmad; Masrukhin, Mohammad Yunus; Sunaryo, Agus; Zaman, Akhmad Roja Badrus (UIN Sunan Kalijaga, 2025)
The renewal of maqāṣid (Islamic legal objectives) emphasizes the substance and purpose of the law, in contrast to ideology, which compels adherence to non-negotiable commitments. This study investigates Yūsuf Al-Qaraḍāwī’s reluctance to apply maqāṣid-based hermeneutics to qaṭʿiyyat al-dilālah (texts with definitive meaning), situating this reluctance within the ideological framework of Islamism to which he remained committed. Through a combined textual and contextual analysis of Al-Qaraḍāwī’s writings and relevant secondary literature, the study demonstrates that his resistance to contextual reinterpretation—reinforced by the status of these texts as qaṭʿiyyah al-wurūd—derives from their construction as immutable foundations of orthodoxy that safeguard the unity of the ummah. This stance serves a dual ideological function: it preserves qaṭʿiyyah texts as fixed boundaries within an Islamic polity and mobilizes them as symbols of pan-Islamic solidarity. Although Al-Qaraḍāwī’s vision of a supranational Islamic state evolved into a transnational authority network through the International Union of Muslim Scholars (IUMS), the underlying ideological imperatives of unity and divine sovereignty remained intact. The article concludes that Al-Qaraḍāwī’s thought exemplifies both the possibilities and limitations of maqāṣid reasoning when situated within the doctrinal commitments of Islamism. This study contributes to a deeper understanding of how Islamic legal thought is transformed into an instrument of ideological legitimation within modern Islamic reformism.